Kerjasama Guru PAK dan Orangtua dalam Membentuk Karakter Siswa - Rully Meifel Mangalengkang; Daniel C. Kambey; Netanel Kaunang (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to identify, analyze, and describe the cooperation between the Christian education teachers and the parents in building the students’ character. This research is a descriptive qualitative research conducted at the Middle School 1, East Amurang in 2020. The data were collected through observation, interviews and documentary study. The results of the analysis and interpretation of the data indicated that: (1). The collaboration between the Christian education teachers and the parents of the students was not optimal; the cooperation that was built was only at school meetings, taking students’ transcripts, and parents' summons when students violated school rules. The parents sometimes did not attend the meetings, even at times picking up students’ transcripts was represented and there was no initiative to contact the Christian education teachers. (2). The supporting factor was the school, namely the teachers of other subjects, the principal and also the school committee who were engaged with the parents. As the inhibiting factor was that of the Christian education teachers themselves, as well as the parents of the students who did not care about the condition of the students. (3). The Christian education teachers in building the character of the students taught in the classroom, gave directions and motivation to the students, coordinated and cooperated with the parents in spite of suboptimality, carried out extracurricular activities and spiritual activities at the school. Meanwhile, the parents at home gave advice and reminded their children to participate in worship services.